Coming soon to theaters Uncharted, Lost Planet, Mass Effect, Everquest. - Gaudiosi, John.
Hollywood has an abysmal track record with its video-game adaptations. Producer Ari Arad hopes to change that with his upcoming films that he hopes are just as spectacular to watch as the game are to play.
Keywords: Video games; Uncharted (Game).; Lost Planet (Game).; Mass Effect (Game).; EverQuest (Computer game).